Growing into pedagogical partnerships over time and across disciplines: My experience as a non-STEM student consultant in STEM courses - Daviduke, Natasha (International Journal for Students as Partners, 2018)
This essay considers the trajectory of my personal and professional growth in my position as a student consultant for three different STEM professors. I explore the unique perspective I brought to this work as a student of the social sciences and I argue for the value of cross-disciplinary pedagogical partnerships.